Levothyroxine malabsorption or pseudomalabsorption? A question in the management of refractory hypothyroidism. Issue 12 (25th November 2022) - Santos Monteiro, Sílvia; Santos, Tiago Silva; Lopes, Ana Martins; Oliveira, José Carlos; Freitas, Cláudia; Couto Carvalho, André
Abstract : Purpose: The levothyroxine absorption test (LT4AT) is an important tool for distinguishing hypothyroidism due to malabsorption from 'pseudomalabsorption' conditions. Our aim was to review our institution's LT4AT results and assess its role in the management of patients with refractory hypothyroidism. Methods: We performed a retrospective study of all patients evaluated for refractory hypothyroidism who underwent LT4AT in our tertiary center between 2014 and 2020. Its results and the impact on thyroid function management during follow-up were assessed. Results: Ten female patients were included with a mean age of 40 years (min-max: 26–62). Mean weight was 72 kg (min–max: 43–88) and baseline LT4 dosage ranged from 2.5 to 5.3 µg/kg/day. The most common causes of hypothyroidism were postsurgical in 50% ( n   = 5) and autoimmune in 20% ( n   = 2). During LT4AT, normal LT4 absorption was found in all but one individual (mean FT4 increase of 231%, min–max: 85–668). The only patient with objective LT4 absorption impairment (maximal increase of 48% by hour 5) presented also Helicobacter pylori gastritis and prior history of 'intestinal surgery' during childhood. No adverse events were reported during any of the LT4ATs. During follow-up (median 11.5 months (IQR 23)), three patients obtained euthyroidism and six had improved their hypothyroidism state. Conclusions: The LT4AT is an effective and safe way to assess refractory hypothyroidism and provides valuable information to distinguish LT4 malabsorption from 'pseudomalabsorption'. Our data suggest that most patients with suspicious LT4 malabsorption perform normally during LT4AT. This test provides relevant information for better management of patients with refractory hypothyroidism.